BEBERAPA MASALAH TENTANG ALAT BUKTI PERSANGKAAN DALAM PENYELESAIAN MASALAH PERDATA - Achmad Feri Hidayatullah (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT As is well known that the general arrangement of the burden of proof in resolving a case, in fact contained in article 163 HIR ketantuan / 283 RBg, which states: "Anyone who says having a right, or refers to an event to affirm that right, or denied another person, that person must prove the existence of the right or the incident ".Evidence (bewijsmiddel) various forms and types, which is able to give a description and explanation of the problems which sued in court. Submitted evidence to justify the arguments of the parties' arguments lawsuit or dispute.From some of the evidence in civil cases there is evidence in at third in the civil evidence is very brief, the evidence conjecture governed by Article 310 RBg / 173 HIR and article 1915 to article 1922 of the Civil Code. Presupposition is the conclusion that by law or by judges drawn from the events that are known to the general direction of an event that is not in general know.Presupposition is the conclusion drawn from an event that has been considered proven or known events, towards an event that has not been proven, if it is an interesting conclusion, the judge is called conjecture conjecture judge ,, whereas if it's interesting conjecture law then called the allegation Constitution.Presupposition can be distinguished as follows:1. suspicions on the basis of the reality / suspicions Judge2. suspicions on the basis of lawsBut in court, the evidence conjecture is dependent upon the assessment of judges and other evidence, so it does not have the strength of evidence was perfect and binding. Keywords:  arranggement, justify